[Crowd at Farmers' Institute Picnic] - Frank Aston::::::photographer::: (1915)
Crowd at the Farmers' Institute (Farmers' Picnic); women and children with picnic spread in eucalyptus grove. 'no. 20' in lower right corner; image from same event published in March 1915 Bulletin (Series II, No. 2)